Cystic pancreatic neuroendocrine tumors: endoscopic ultrasound and fine-needle aspiration characteristics - Yoon, W. J.; Daglilar, E. S.; Pitman, M. B.; Brugge, W. R. (Endoscopy, 2013)
Background and study aims: Limited data are available on the endoscopic ultrasound (EUS) and fine-needle aspiration (FNA) characteristics of cystic pancreatic neuroendocrine tumors (CPanNets). The aims of this study were to describe the EUS and FNA characteristics of pathologically confirmed CPanNets and to compare these characteristics with mucinous cysts from matched patients.Patients and methods: From an EUS – FNA database (between 1999 and 2011), 19 patients with a pathologically confirmed CPanNet were identified. Patient characteristics, cyst fluid carcinoembryonic antigen (CEA) levels, pathology, and EUS findings were analyzed. For comparison, age- and sex-matched patients with mucinous cysts were randomly chosen from the same database.Results: Of the 19 patients, two had multiple endocrine neoplasia type 1 and two had metastases. The median diameter of the lesions was 24 mm. EUS revealed unilocular lesions in 7 patients, thinly septated lesions with thin walls in 1, and mixed solid-cystic lesions in 11. EUS – FNA cytology confirmed neoplasm in 12 of the 19 patients (63.2 %). The median cyst fluid CEA level (n = 15) was 1.1 ng/mL (range 0.3 – 500 ng/mL). Compared with matched patients with mucinous cysts, the median cyst fluid CEA was lower (1.1 ng/mL vs. 400 ng/mL), thick walls were more common (66.7 % vs. 13.3 %), and diagnostic cytology was more likely (73.3 % vs. 20.0 %).Conclusions: Analysis of EUS and FNA results showed that the cyst fluid from CPanNets had a lower CEA concentration, a higher frequency of thick walls on EUS, and higher diagnostic cytology compared with mucinous cysts. These findings may aid in the diagnosis of CPanNets.